Feminist approaches to situated knowledge production: Urban flood management in Can Tho City, Vietnam - Ly Quoc Dang; Kawarazuka, Nozomi (Elsevier, 2025)
The main objective of this chapter is to identify and understand how women use knowledge about flooding as a tool for agency and empowerment. The concept we use is women’s empowerment linked to women’s agency and their situated knowledge during floods. These concepts are applied through the intersection of gender, class, age, and disability. Qualitative data collection included a household survey, in-depth interviews with women and relevant actors, and participant observation. We found that women were able to leverage their knowledge to reshape flood outcomes. Women who were successful in this regard used knowledge areas such as learning from their own experience and others and mobilizing resources through social networks to achieve their goals. During the floods, their concerns and experiences are closely related to their gender roles and responsibilities in childcare and housework. Women coped well with caring for their children and doing housework, among other productive and reproductive activities. Another experience is related to their bodies, and the women expressed the 13 different emotional feelings they used to negotiate with their husbands, relatives, neighbors, local authorities, and others to reduce flood risks and address flood situations. The last experience was related to their role in household financial management. Women were the ones who saved, loaned, and borrowed money from different people to contribute to flood management. Regarding the participation of women in social networks, we found that women engaged and proposed new technical solutions to reduce the risks of flooding disasters through negotiations with their friends, neighbors, relatives, and other community members. In addition, they used different social networks to communicate to obtain information related to flood risks and management. Among the women who participated in this research, older and disabled women were more marginalized and less able to overcome flooding than other women due to their physical limitations and lower levels of social and family support. These women have a risk of being further marginalized through increasing climate-induced disasters. Specific policies and development programs are therefore required to help empower these most vulnerable women.